Study on the Association between Tail Lesion Score, Cold Carcass Weight, and Viscera Condemnations in Slaughter Pigs - Teixeira, Dayane Lemos; Harley, Sarah; Hanlon, Alison; O’Connell, Niamh Elizabeth; More, Simon John; Manzanilla, Edgar Garcia; Boyle, Laura Ann (Frontiers in Veterinary Science, 2016)
The aim of this study was to assess the relationship between tail lesions, cold carcass weight and viscera condemnations in an Irish abattoir. The following data were collected at the evisceration point from every 3rd pig slaughtered over 7 days: farm identification, sex, tail lesion score, viscera inspection outcome and cold carcass weight. Tail lesions were scored according to a 5 point scale. Disease lesions responsible for lung (pleurisy, pneumonia and abscess), heart (pericarditis) and liver (ascariasis) condemnation were recorded based on the decision of the veterinary inspector. Data on 3,143 pigs from 61 batches were available. The relationship between disease lesions, tail lesion score and cold carcass weight was studied at individual carcass level, whereas the relationship between disease lesions and tail lesion score was studied at both carcass and batch level. Tail lesions (score ≥ 1) were found in 72% of the study population, with 2.3% affected by severe tail lesions (scores ≥ 3). Pleurisy (13.7%) followed by pneumonia (10.4%) showed the highest prevalence, whereas the prevalence of ascariasis showed the greatest variation between batches (0 to 75%). Tail lesion score, pleurisy, pleuropneumonia and pericarditis were associated with reductions in carcass cold weight (P ≤ 0.05) ranging from 3 to 6.6 kg. Tail lesion score was associated with condemnations for pleurisy, pneumonia and pleuropneumonia (P ≤ 0.05) at a batch level. Veterinary inspector shift was associated with condemnations for pneumonia, pleuropneumonia and pericarditis (P ≤ 0.05) at a carcass level and with pneumonia at a batch level. Sex was not associated with viscera condemnations but males were more likely to be affected by tail lesions. The relationship between overall tail lesion score and the lung diseases at batch level supports the relationship between poor health and poor welfare of pigs on farms. The inclusion of tail lesion scores at post mortem meat inspection should be considered as a health and welfare diagnostic tool.